Using a problem-based learning model assisted by comic media to improve students’ learning outcomes on the topic of the relationship between addition and subtraction - Pradana, I Gde Andika Yudha; Muhardini, Sintayana; Ahyansyah, Ahyansyah (Jurnal Ilmiah Mandala Education (JIME), 2025)
The Problem Based Learning Model is designed to assist students in building a flexible and broad knowledge base, developing effective problem solving skills, developing independent learning as a lifelong learning skill, becoming effective collaborators and being intrinsically motivated to learn. But in reality, not all teachers use this learning model in the learning process in their class. This learning model is very suitable if combined with the use of comic media in addition and subtraction relationship material because it increases student motivation and focus due to creative, innovative and contextual teaching materials. This classroom action research was carried out with the aim of finding out whether the problem-based learning model assisted by comic media can improve student learning outcomes on the topic of the relationship between addition and subtraction. The participants involved were 22 grade 3 elementary school students in Tabanan Regency. The research instrument was in the form of reflection sheets, learning improvement plans, evaluation question sheets for each cycle which were answered by students. Data analysis uses observation and documentation techniques from student learning outcomes documents at the end of the learning process of each cycle where students who get a score ≥ 70 are categorized as complete, and those who get < 70 are categorized as incomplete. For students' classical learning completeness is determined based on the percentage of students' learning completeness in class, namely at least 80%. This discovery will provide alternative uses of media and learning strategies to fellow educators to be able to have an impact on improving the learning outcomes of the students they teach.